2007
DOI: 10.1080/02841860600731935
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, clinical and treatment related predictors for event-free probability following low-dose radiotherapy for painful heel spurs – a retrospective multicenter study of 502 patients

Abstract: Kundt (2007) Demographic, clinical and treatment related predictors for event-free probability following low-dose radiotherapy for painful heel spurs -a retrospective multicenter study of 502 patients, Acta Oncologica, 46:2, 239-246,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 32 publications
3
33
0
1
Order By: Relevance
“…To the best of our knowledge, in no study, an influence of gender on treatment outcome has been confirmed [22,24,30,38,39]. In contrast to radiotherapy for oncological indications with high doses, efficacy and tolerability of LD-EBRT seems to be the same concerning gender.…”
Section: Gendermentioning
confidence: 91%
See 4 more Smart Citations
“…To the best of our knowledge, in no study, an influence of gender on treatment outcome has been confirmed [22,24,30,38,39]. In contrast to radiotherapy for oncological indications with high doses, efficacy and tolerability of LD-EBRT seems to be the same concerning gender.…”
Section: Gendermentioning
confidence: 91%
“…Since 1937 [21] for decades, large retrospective studies on the efficacy of LD-EBRT in calcaneodynia have been published (overview in 22). In 1970, one negative randomized trial was reported and heavily criticized but had not been repeated [23].…”
Section: Results Of Randomized Trials On Radiotherapy For Painful Heementioning
confidence: 99%
See 3 more Smart Citations